Functional copper foil current collector and preparation method and application thereof
By controlling the thickness and grain size of the copper layer in the copper foil current collector, the residual stress of the functional copper foil current collector in the lithium battery is reduced, and the problems of reduced battery cycle life and safety performance are solved, achieving better mechanical performance and stability.
Patent Information
- Application Number
- CN202510192069.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Functional copper foil current collectors in existing lithium batteries are prone to generate residual stress during the electroplating process, resulting in reduced battery cycle life and safety performance.
By controlling the thickness and grain size of the first copper layer and the second copper layer, the residual stress of the functional copper foil current collector is reduced. The specific method includes depositing a first copper layer and a second copper layer on a polymer film, respectively, controlling its thickness and grain size within a specific range to reduce stresses generated during the deposition process.
It effectively reduces the risk of residual stress failure of functional copper foil current collectors, improves its mechanical properties and stability, thereby extending the service life of the battery and improving cycle performance and safety performance.
Smart Images

Figure CN119695168A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium battery current collectors, and specifically relates to a functional copper foil current collector and a preparation method and application thereof. Background Art
[0002] With the rapid development of new energy and electronic technology, the cycle life, safety performance, energy density, etc. of batteries have become top priorities. As a very important part of the battery, the current collector is used to collect the current generated by the active materials of the battery in order to form a larger current output. Its performance will directly affect the cycle life, energy density, safety, etc. of the battery.
[0003] At present, the positive and negative electrodes in lithium batteries and sodium batteries mostly use copper foil and aluminum foil as current collectors. This type of current collector has high cost and quality, which is not conducive to controlling battery costs and improving energy density. In this regard, composite foil has obvious advantages over traditional foils. Composite foil current collectors are usually a "sandwich" structure, with a polymer high molecular layer as the inner layer and metal conductive layers on both sides. Since the metal layer on the surface of the composite current collector is thinner and the polymer layer inside is lighter, it can greatly reduce the overall weight of the current collector, thereby increasing the energy density of the lithium-ion battery; at the same time, the thinner metal layer on the surface of the composite current collector is easier to disconnect than the traditional foil current collector when the lithium-ion battery has thermal runaway, thereby isolating the connection between the active material and the current collector and preventing the lithium-ion battery from continuing thermal runaway.
[0004] Although composite foil has the advantages of low cost and light weight, the functional copper foil current collector will produce residual stress during the electroplating process due to reasons such as too fast deposition rate, which will lead to stress deformation of the film after electroplating, increase the risk of copper layer falling off, and thus reduce the cycle life and safety performance of the battery. Summary of the invention
[0005] In order to solve the problems and shortcomings in the prior art, the present invention provides a functional copper foil current collector and a preparation method and application thereof. The functional copper foil current collector has lower residual stress and thus has better mechanical properties and stability, thereby improving the service life of the functional copper foil current collector, thereby improving the cycle performance and safety performance of the battery.
[0006] According to a first aspect of the present invention, a functional copper foil current collector is provided, comprising a polymer film, a first copper layer, and a second copper layer, wherein the first copper layer is arranged on both sides of the polymer film, and the second copper layer is arranged on the surface of the first copper layer; the residual stress of the functional copper foil current collector is not higher than 5.5 MPa; the thickness d1 of the first copper layer is 50~140nm, and the grain size a1 is 20~60nm; the thickness d2 of the second copper layer is 100~200nm, and the grain size a2 is 100~200nm.
[0007] Functional foil current collectors are usually "sandwich" structures, usually with a polymer film as the base film, and metal conductive layers deposited on both sides. Generally, the metal conductive layer is deposited on the polymer film by magnetron sputtering deposition or electroplating deposition. Whether it is magnetron sputtering deposition or electroplating deposition, a certain residual stress will be generated, which will affect the mechanical properties and stability of the composite foil current collector. The generation of residual stress is related to many factors, including the deposition process of the film, the properties of the substrate, and subsequent processing steps. During the magnetron sputtering and electroplating process, the mismatch in thermal expansion coefficients and lattice structure between the film and the substrate may lead to the generation of residual stress. In addition, the thickness of the film is also an important factor, because thicker films are more likely to produce residual stress.
[0008] In order to ensure the uniformity and stability of the deposited film in the functional foil current collector, multiple or the same deposition methods are used to deposit multiple metal conductive layers. During the multiple deposition processes, more residual stress is often generated due to the multiple depositions, resulting in a decrease in the performance of the composite current collector.
[0009] In the functional copper foil current collector provided by the present invention, a first copper layer and a second copper layer are respectively provided on both sides of the polymer film, which respectively control the thickness of the two copper layers and the grain size therein, so that the residual stress of the final functional copper foil current collector is controlled within a smaller range, which can effectively reduce the risk of failure of the functional copper foil current collector due to residual stress. Specifically, the first copper layer is thinner and has a smaller grain size, which can effectively reduce the residual stress caused by the different materials of the polymer base film and the first copper layer deposition layer. The second copper layer is thicker and has a larger grain size. Because it is deposited on the same material as the first copper layer, if the grain size is too small, it will cause the membrane surface structure to be too compact, and the tensile stress will increase during film formation, thereby causing an increase in overall stress. Therefore, the grain size of the second copper layer is controlled to be smaller than that of the first copper layer, which can reduce the overall residual stress of the product after film formation.
[0010] Moreover, the present invention further discovered that if the grain size in the first copper layer and the second copper layer is smaller than the above ranges, it will also lead to an increase in residual stress, because the finer the grains, the larger the grain boundary area, which increases the possibility of stress concentration, and also leads to uneven deformation, increased thermal stress, etc., thereby increasing residual stress. If the grain size in the first copper layer and the second copper layer is larger than the above ranges, it will also lead to an increase in residual stress, because the displacement and reorganization of the grain boundaries during the grain growth process lead to changes in the internal stress state. Specifically, the growth of grains is a gradual and slow process, but in some cases, such as when the temperature is too high or the time is too long, the grains will suddenly grow, and this sudden growth is often accompanied by changes in internal stress, thus leading to an increase in residual stress.
[0011] In addition, the thickness of the first copper layer and the second copper layer will also have a certain effect on the residual stress of the functional copper foil current collector. Specifically, the thickness of the copper layer of the functional copper foil current collector will affect the uniformity and ductility of the coating, thereby affecting the distribution and size of the residual stress. When the copper layer is thin, the coating may not be uniform enough, resulting in uneven stress distribution; when the copper layer is thick, although it can provide better mechanical properties, it may also increase residual stress and affect the fatigue strength and service life of the material. Therefore, it is necessary to keep the thickness of the first copper layer and the second copper layer within a certain range, which can be more conducive to reducing residual stress and optimizing various aspects of the performance of the functional copper foil current collector.
[0012] Preferably, the bonding force of the functional copper foil current collector is 200~300N / m. The bonding force of the current collector has an important influence on the performance of lithium-ion batteries. Whether the bonding force is too large or too small, it will have a negative impact on the performance of the battery. If the bonding force is too small, the contact between the pole piece and the functional copper foil current collector is not close enough, and the current cannot be transmitted effectively, which reduces the performance and life of the battery. If the bonding force is too large, firstly, the excessively strong bonding force will increase the internal resistance of the battery, making current transmission more difficult. This will not only affect the performance of the battery, but may also shorten the cycle life of the battery. Secondly, if the bonding force is too large, it may also cause the pole piece to separate from the current collector, because the excessively strong bonding force may cause excessive stress on the material during the use of the battery, and ultimately cause the battery to fail.
[0013] Preferably, the thickness of the polymer film is 4~6μm. The thickness of the polymer film will also affect the residual stress of the functional copper foil current collector to a certain extent. If the polymer film base material is too thin, it may lead to a decrease in mechanical properties and an increase in residual stress, deteriorating the mechanical properties and stability of the composite current collector. If the polymer film base material is too thick, although it may provide better mechanical support, it may also introduce unnecessary residual stress, which will also affect the mechanical properties and stability of the composite current collector.
[0014] Preferably, the material of the polymer film includes at least one of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyethylene, polypropylene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, polyphenylene sulfide, polyphenylene oxide, polystyrene, and polyimide.
[0015] According to a second aspect of the present invention, there is provided a method for preparing the above-mentioned functional copper foil current collector, comprising the following steps: S1. After a polymer film is pre-treated by plasma cleaning, a first copper layer is plated on both sides of the polymer film by magnetron sputtering; during the magnetron sputtering process, the temperature of the polymer film is controlled to be maintained at -18~-22°C, and the magnetron sputtering rate is 1~2nm / s; S2. Then, a second copper layer is plated on both sides of the product obtained in S1 by wet electroplating; during the wet electroplating process, the temperature of the plating solution is maintained at 24~26°C, the plating rate is 1~3nm / s, and the plating rate is controlled to be greater than the magnetron sputtering rate, so as to obtain a functional copper foil current collector.
[0016] In the preparation method of the functional copper foil current collector provided above, the first copper layer is first deposited by magnetron sputtering, and then the second copper layer is deposited on this basis by wet electroplating. First, the polymer film is pre-treated by plasma cleaning, and the surface of the polymer film is cleaned and treated by the interaction between plasma and the surface of the polymer film material, thereby improving the surface cleanliness of the polymer film substrate material and enhancing the adhesion.
[0017] Then magnetron sputtering is performed on the surface of the polymer film to deposit the first copper layer. Since the sputtering of copper atoms during the magnetron sputtering process will generate a lot of heat, the temperature of the polymer film matrix material needs to be controlled in a low range. However, if the temperature is too low, the polymer film matrix material will not be able to withstand stress and will crack. Selecting -18~-22℃ can not only effectively reduce the adverse effects caused by heat generation during magnetron sputtering, but also effectively improve the stress resistance of the polymer film matrix material and prevent it from cracking. At the same time, during the magnetron sputtering process, a deposition rate that is too high will cause the grain size to be too large, resulting in excessive compressive stress or poor bonding. A deposition rate that is too low will affect production efficiency and will also generate greater tensile stress. And a too low deposition rate will cause the metal layer to quickly "stress freeze" after deposition, and the stress cannot be released during the deposition process, resulting in greater stress. Therefore, controlling the magnetron sputtering rate between 1~2nm / s can ensure that the grain size of the first copper layer is between 100~250nm, effectively reducing the residual stress of the deposited first copper layer.
[0018] After the first copper layer is deposited by magnetron sputtering, the second copper layer is deposited on this basis by wet electroplating. During the electroplating process, if the temperature of the electroplating solution is too high or too low, the brightener and leveler in the electroplating solution will fail, resulting in uneven film thickness, which in turn leads to increased stress. In the electroplating process, the temperature rise will increase the electroplating rate, resulting in coarsening of the crystals, and the temperature drop will reduce the solubility of copper in the electroplating solution, resulting in more residual stress on the film surface particles, so the plating solution temperature needs to be controlled at 24~26 degrees Celsius. As the grain size increases, the film surface structure will become loose at a high growth rate, thereby increasing the compressive stress. At a low growth rate, the film surface structure will be too compact, and the tensile stress will increase during film formation, resulting in an increase in overall stress. Therefore, the electroplating rate during the electroplating process must also be controlled within a certain range of measured values. Moreover, since the electroplating layer is formed secondary on the magnetron layer, the grain size and deposition rate of the magnetron film copper layer must be kept smaller than those of the electroplating layer copper layer to alleviate the overall residual stress of the functional copper foil current collector, effectively reduce the residual stress, and improve the mechanical properties and stability of the functional copper foil current collector.
[0019] Preferably, in S1, the specific operation of the plasma cleaning pretreatment is: placing the polymer film in a vacuum of 2×10 -4 ~8×10 -3 Under the condition of Pa, argon gas is introduced with a flow rate of 80~100sccm and the processing time is 5~10s.
[0020] Preferably, in S2, during the wet electroplating process, the electroplating solution includes 90-110 g / L copper sulfate, 110-130 g / L sulfuric acid, 40-60 mg / L hydrochloric acid, and 105-350 mg / L copper plating additives; the copper plating additives include 50-100 mg / L accelerator, 5-50 mg / L leveler, and 50-200 mg / L inhibitor. The composition of the electroplating solution will also affect the grain size in the electroplated copper layer and the uniformity and film-forming properties of the electroplated copper layer, thereby affecting the residual stress of the functional copper foil current collector, and affecting its mechanical properties and stability. Therefore, it is necessary to control the composition of the electroplating solution to ensure that the electroplated copper layer has a more suitable grain size and the electroplated copper layer has better uniformity and film-forming properties.
[0021] Preferably, in S2, the electroplating solution includes 100 g / L copper sulfate, 120 g / L sulfuric acid, 50 mg / L hydrochloric acid, 80 mg / L accelerator, 30 mg / L leveler, and 100 mg / L inhibitor.
[0022] In summary, the functional copper foil current collector provided by the present invention has a relatively suitable residual stress, which can effectively reduce the risk of failure of the functional copper foil current collector due to residual stress. Therefore, the functional copper foil current collector provided by the present invention has good mechanical properties and stability, and can maintain the original structural state for a long time during the battery charge and discharge cycle, which can further optimize the battery's cycle performance and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic diagram of the structure of the functional copper foil current collector in the present invention.
[0024] The reference numerals are: 1 - polymer film; 2 - first copper layer; 3 - second copper layer. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.
[0026] Example 1 The functional copper foil current collector of this embodiment is prepared according to the following steps: S1. Take a 4.5μm PP (polypropylene) base film, ensure that its surface is flat and free of impurities, perform plasma cleaning pretreatment on it, then wind the PP base film on the main roller of the magnetron sputtering equipment, start the sputtering process, keep the temperature of the PP base film at -20℃, and plate a 90nm thick first copper layer on the upper and lower surfaces of the PP base film at a deposition rate of 1.2nm / s; the specific operation of the plasma cleaning pretreatment is: place the PP base film in a vacuum degree of 2×10 -4 Under the condition of Pa, argon gas with a flow rate of 90 sccm was introduced and the processing time was 10 s; S2. Place the film material with the first copper layer sputtered in a water plating tank with a constant temperature of 25°C, where the plating solution includes 100g / L copper sulfate, 120g / L sulfuric acid, 50mg / L hydrochloric acid, and copper plating additives (including 80mg / L accelerator, 30mg / L leveler, 100mg / L inhibitor) for electroplating, and plate a 1μm thick second copper layer on the upper and lower surfaces of the film material with the first copper layer sputtered at a deposition rate of 1.4nm / s to obtain a functional copper foil current collector. Figure 1 , Figure 1 Schematic diagram of the structure of the functional copper foil current collector prepared in this embodiment. The schematic diagrams of the structures of the functional copper foil current collectors prepared in other embodiments and comparative examples are also referred to Figure 1 .
[0027] The functional copper foil current collector obtained in this embodiment was tested for residual stress and grain sizes of the first copper layer and the second copper layer, and the bonding force of the functional copper foil current collector was also tested.
[0028] Among them, the residual stress of the functional copper foil current collector provided in this embodiment is tested by the μ-360s X-ray residual stress tester of QUANTUM Quantum Scientific Instrument Trading (Beijing) Co., Ltd. The specific operation is as follows: set the 2θ scanning range to 30° to 90°, the scanning speed can be set between 5 degrees per minute, and the step size is set to 0.01°. Change the ψ angle at an angle interval of 15°, perform X-ray diffraction measurement on the sample at each ψ angle, and record the corresponding diffraction angle 2θ and diffraction intensity data. When ψ=0°, the detector is located at the theoretically calculated diffraction angle 2θ, at which time the incident line and the diffraction line are symmetrically radially configured relative to the normal line of the sample surface; when ψ≠0°, first turn the sample clockwise through the specified ψ angle, the detector is still at 0, and then perform θ~2θ linkage scanning. According to the measured diffraction angle 2θ data at different ψ angles, 2θ is used as the ordinate and sin²ψ is used as the abscissa to draw a graph, and the slope m of the straight line is obtained by least squares fitting. Combined with the diffraction stress coefficient k = -300Mpa / ra of the copper film (111), the residual stress value σ = k*m of the copper film is calculated. Since k < 0, when m < 0, it is tensile stress, when m > 0, it is compressive stress, and when m = 0, there is no stress.
[0029] The functional copper foil current collector of this embodiment was subjected to grain size scanning test using the Cypher series atomic force microscope of Oxford Instruments Group. The specific operating conditions are as follows: scanning range: 3-10 microns. Scanning speed: 10 Hz. Amplitude setting: 50 nanometers. After scanning, the grains and grain boundaries were distinguished by the grayscale value of the image. For each identified grain, the grain size was measured using the measurement tool provided by the atomic force microscope software.
[0030] The adhesion of the functional copper foil current collector provided in this embodiment was tested using the Elcometer 510 automatic pull-off adhesion tester produced by the British Elcometer company. Refer to ASTM B533: American Society for Testing and Materials "Standard Test Method for Peel Strength of Metal Electroplated Plastics". Specifically as follows: Use a universal testing machine to cut a sample with a width of (25.0±0.25) mm from the composite current collector material, install the prepared sample on the fixture of the test equipment, the peeling angle is 90°, the test speed is 100 mm / min, and the peeling force is divided by the width of the sample to obtain the peeling strength per unit width (N / m).
[0031] The above tests show that in the functional copper foil current collector of this embodiment, the grain size of the first copper layer is 40 nm, the grain size of the second copper layer is 130 nm, the residual stress is 3.8 MPa, and the bonding force is 241 N / m.
[0032] Example 2 The process of preparing the functional copper foil current collector of this embodiment is the same as that of embodiment 1 except that, in S1, during the process of forming the first copper layer by magnetron sputtering, the deposition rate is controlled to be 2 nm / s, and the thickness of the first copper layer is also 90 nm. The rest of the operations are the same as those of embodiment 1.
[0033] The functional copper foil current collector prepared in this embodiment is also tested for residual stress, grain size of the first copper layer and the second copper layer, and adhesion. The specific test method is as in Example 1.
[0034] After testing, it was found that in the functional copper foil current collector of this embodiment, the grain size of the first copper layer was 28 nm, the grain size of the second copper layer was 110 nm, the residual stress was 3.5 MPa, and the bonding force was 266 N / m.
[0035] Example 3 The process of preparing the functional copper foil current collector of this embodiment is different from that of Embodiment 1 only in that: in S1, during the process of forming the first copper layer by magnetron sputtering, the deposition rate is controlled to be 1 nm / s, and the thickness of the first copper layer is also 90 nm. The rest of the operations are the same as those of Embodiment 1.
[0036] The functional copper foil current collector prepared in this embodiment is also tested for residual stress, grain size of the first copper layer and the second copper layer, and adhesion. The specific test method is as in Example 1.
[0037] After testing, it was found that in the functional copper foil current collector of this embodiment, the grain size of the first copper layer was 38 nm, the grain size of the second copper layer was 180 nm, the residual stress was 4.2 MPa, and the bonding force was 225 N / m.
[0038] Example 4 The process of preparing the functional copper foil current collector of this embodiment is different from that of embodiment 1 only in that in S2, during the process of forming the second copper layer by wet electroplating, the deposition rate is controlled to be 1 nm / s, and the thickness of the second copper layer is also 1 μm. The rest of the operations are the same as those of embodiment 1.
[0039] The functional copper foil current collector prepared in this embodiment is also tested for residual stress, grain size of the first copper layer and the second copper layer, and adhesion. The specific test method is as in Example 1.
[0040] After testing, it was found that in the functional copper foil current collector of this embodiment, the grain size of the first copper layer was 30 nm, the grain size of the second copper layer was 120 nm, the residual stress was 3.3 Mpa, and the bonding force was 256 N / m.
[0041] Example 5 The process of preparing the functional copper foil current collector of this embodiment is different from that of embodiment 1 only in that in S2, during the process of forming the second copper layer by wet electroplating, the deposition rate is controlled to be 3 nm / s, and the thickness of the second copper layer is also 1 μm. The rest of the operations are the same as those of embodiment 1.
[0042] The functional copper foil current collector prepared in this embodiment is also tested for residual stress, grain size of the first copper layer and the second copper layer, and adhesion. The specific test method is as in Example 1.
[0043] After testing, it was found that in the functional copper foil current collector of this embodiment, the grain size of the first copper layer was 40 nm, the grain size of the second copper layer was 200 nm, the residual stress was 4.8 MPa, and the bonding force was 222 N / m.
[0044] Example 6 The process of preparing the functional copper foil current collector of this embodiment is different from that of Embodiment 1 only in that: in S1, the material of the polymer film is polyethylene terephthalate. The rest of the operations are the same as those of Embodiment 1.
[0045] The functional copper foil current collector prepared in this embodiment is also tested for residual stress, grain size of the first copper layer and the second copper layer, and adhesion. The specific test method is as in Example 1.
[0046] After testing, it was found that in the functional copper foil current collector of this embodiment, the grain size of the first copper layer was 50 nm, the grain size of the second copper layer was 150 nm, the residual stress was 3.6 MPa, and the bonding force was 266 N / m.
[0047] Example 7 The process of preparing the functional copper foil current collector of this embodiment is different from that of Embodiment 1 only in that: in S1, the material of the polymer film is polyvinylidene fluoride. The rest of the operations are the same as those of Embodiment 1.
[0048] The functional copper foil current collector prepared in this embodiment is also tested for residual stress, grain size of the first copper layer and the second copper layer, and adhesion. The specific test method is as in Example 1.
[0049] After testing, it was found that in the functional copper foil current collector of this embodiment, the grain size of the first copper layer was 50 nm, the grain size of the second copper layer was 150 nm, the residual stress was 3.7 MPa, and the bonding force was 242 N / m.
[0050] Example 8 The process of preparing the functional copper foil current collector of this embodiment is different from that of Embodiment 1 only in that: in S1, the material of the polymer film is polyimide. The rest of the operations are the same as those of Embodiment 1.
[0051] The functional copper foil current collector prepared in this embodiment is also tested for residual stress, grain size of the first copper layer and the second copper layer, and adhesion. The specific test method is as in Example 1.
[0052] After testing, it was found that in the functional copper foil current collector of this embodiment, the grain size of the first copper layer was 50 nm, the grain size of the second copper layer was 150 nm, the residual stress was 3.5 MPa, and the bonding force was 222 N / m.
[0053] Example 9 The process of preparing the functional copper foil current collector of this embodiment is different from that of Embodiment 1 only in that: in S1, the material of the polymer film is polyphenylene sulfide. The rest of the operations are the same as those of Embodiment 1.
[0054] The functional copper foil current collector prepared in this embodiment is also tested for residual stress, grain size of the first copper layer and the second copper layer, and adhesion. The specific test method is as in Example 1.
[0055] After testing, it was found that in the functional copper foil current collector of this embodiment, the grain size of the first copper layer was 50 nm, the grain size of the second copper layer was 150 nm, the residual stress was 4 MPa, and the bonding force was 242 N / m.
[0056] Example 10 The process of preparing the functional copper foil current collector of this embodiment is different from that of Embodiment 1 only in that: in S1, during the process of forming the first copper layer by magnetron sputtering, the deposition rate is controlled to be 3 nm / s, and the thickness of the first copper layer is also 90 nm. The rest of the operations are consistent with those of Embodiment 1.
[0057] The functional copper foil current collector prepared in this embodiment is also tested for residual stress, grain size of the first copper layer and the second copper layer, and adhesion. The specific test method is as in Example 1.
[0058] After testing, it was found that in the functional copper foil current collector of this embodiment, the grain size of the first copper layer was 60nm, the grain size of the second copper layer was 150nm, the residual stress was 5.2Mpa, and the bonding force was 290N / m.
[0059] Comparative Example 1 The process of preparing the functional copper foil current collector of this comparative example is different from that of Example 1 only in that in S1, during the process of forming the first copper layer by magnetron sputtering, the deposition rate is controlled to be 4 nm / s, and the thickness of the first copper layer is also 90 nm. The rest of the operations are the same as those of Example 1.
[0060] The functional copper foil current collector prepared in this comparative example was also tested for residual stress, grain size of the first copper layer and the second copper layer, and adhesion. The specific test methods refer to Example 1.
[0061] After testing, it was found that in the functional copper foil current collector of this comparative example, the grain size of the first copper layer was 70 nm, the grain size of the second copper layer was 250 nm, the residual stress was 7.9 MPa, and the bonding force was 131 N / m.
[0062] Comparative Example 2 The process of preparing the functional copper foil current collector of this comparative example is different from that of Example 1 only in that in S2, during the process of forming the second copper layer by wet electroplating, the deposition rate is controlled to be 5 nm / s, and the thickness of the second copper layer is also 1 μm. The rest of the operations are the same as those of Example 1.
[0063] The functional copper foil current collector prepared in this comparative example was also tested for residual stress, grain size of the first copper layer and the second copper layer, and adhesion. The specific test methods refer to Example 1.
[0064] After testing, it was found that in the functional copper foil current collector of this comparative example, the grain size of the first copper layer was 66 nm, the grain size of the second copper layer was 430 nm, the residual stress was 8.8 MPa, and the bonding force was 111 N / m.
[0065] Comparative Example 3 The process of preparing the functional copper foil current collector of this comparative example is different from that of Example 1 only in that in S1, during the process of forming the first copper layer by magnetron sputtering, the deposition rate is controlled to be 6 nm / s, and the thickness of the first copper layer is also 90 nm. The rest of the operations are consistent with those of Example 1.
[0066] The functional copper foil current collector prepared in this comparative example was also tested for residual stress, grain size of the first copper layer and the second copper layer, and adhesion. The specific test methods refer to Example 1.
[0067] After testing, it was found that in the functional copper foil current collector of this comparative example, the grain size of the first copper layer was 88 nm, the grain size of the second copper layer was 320 nm, the residual stress was 10.8 MPa, and the bonding force was 103 N / m.
[0068] Comparative Example 4 The only difference from Example 1 in the process of preparing the functional copper foil current collector of this comparative example is that a first copper layer with a thickness of 90 nm is plated on the upper and lower surfaces of the PP base film at a deposition rate of 0.1 nm / s. The rest of the operations are the same as those of Example 1.
[0069] The functional copper foil current collector prepared in this comparative example was also tested for residual stress, grain size of the first copper layer and the second copper layer, and adhesion. The specific test methods refer to Example 1.
[0070] After testing, it was found that in the functional copper foil current collector of this comparative example, the grain size of the first copper layer was 5 nm, the grain size of the second copper layer was 40 nm, the residual stress was 6.2 MPa, and the bonding force was 84 N / m.
[0071] Test Case 1. Experimental Construction Method (1) The tensile strength of the composite current collectors prepared in the above embodiments and comparative examples was tested using an electronic universal material testing machine. The test temperature was room temperature. The test conditions were a gauge length of 10 mm, a tensile speed of 100 mm / min, and a width of 15 mm. Other requirements were measured according to the method specified in GB / T 1040.3-2006.
[0072] (2) A battery is prepared using the functional copper foil current collector prepared in the above embodiment and comparative example. The specific steps of preparing the battery are as follows: Preparation of positive electrode sheet: NCM811, carbon nanotubes and PVDF are mixed evenly in N-methylpyrrolidone solvent at a mass ratio of 96:2:2 to prepare positive electrode slurry, and the positive electrode slurry is coated on a metal aluminum foil, and then rolled, slit and die-cut to prepare positive electrode sheets.
[0073] Preparation of negative electrode sheet: artificial graphite, Super P and carboxymethyl cellulose are mixed uniformly in water at a mass ratio of 95.5:1:3.5 to prepare negative electrode slurry, and the negative electrode slurry is coated on the functional copper foil current collector prepared in the above embodiment or comparative example, and rolled, slit and die-cut to prepare negative electrode sheet.
[0074] Preparation of the battery: Assemble the positive and negative electrodes and the separator prepared above together to form a bare cell. Winding is to wind the electrode and separator into a cylindrical shape, and lamination is to alternately stack the electrode and separator into a multi-layer structure. Then, the bare cell is loaded into the battery shell for welding and packaging. Then, the electrolyte is injected into the battery shell. Finally, the battery is formed and fixed.
[0075] The cycle capacity retention rate of each prepared battery was tested, and the specific test conditions were as follows: Prepare test equipment: Prepare an ITECH IT8500+ series test equipment. The system should have functions such as constant current charging, constant voltage charging, and constant current discharging, and be able to monitor and record battery voltage, current, capacity and other parameters in real time. In addition, it is also necessary to prepare temperature control equipment, such as a constant temperature box, to ensure that the test process is carried out under the set temperature conditions.
[0076] Determine the test conditions: select the common test temperature of 55°C, the charge and discharge rate of 1C, and the charge and discharge cut-off voltage according to the battery specification.
[0077] Battery activation: Perform several charge and discharge cycles on new batteries or batteries that have not been used for a long time to activate the chemical reaction inside the battery and stabilize its performance. The charge and discharge rate and cut-off voltage of activation can be carried out according to normal test conditions, but the number of cycles is generally 3 to 5 times.
[0078] Initial capacity test: After the activated battery is fully charged, discharge the battery to the cut-off voltage according to the set discharge rate, and record the capacity data during the discharge process as the initial capacity of the battery. In order to improve the accuracy of the test, it is recommended to perform 5 discharge tests and take the average value as the initial capacity C0.
[0079] Cycle test: Charging process: Use the battery test system to charge the battery at a constant current according to the set charging rate and cut-off voltage. When the battery voltage reaches the set cut-off voltage, switch to constant voltage charging until the charging current drops to 0.05 of the set cut-off current, then stop charging.
[0080] Discharge process: After charging is completed, let it stand for a period of time (such as 30 minutes) to allow the chemical reaction inside the battery to reach a balanced state. Then discharge the battery to a cut-off voltage of 1V according to the set discharge rate, and record the capacity data Cn (where n is the number of cycles) during the discharge process.
[0081] Cycle number: Repeat the above charge and discharge process for n=1000 times, and record the capacity data C at this time 1000 .
[0082] Data recording and analysis: Capacity retention rate calculation: based on the average capacity data C of the last ten discharges 1000 and initial capacity, and calculate the cycle capacity retention rate of the battery according to the following formula: Capacity retention rate = C 1000 / C0×100%.
[0083] 2. Experimental results The relevant properties of the functional copper foil current collectors prepared in all the above embodiments and comparative examples and the batteries prepared therewith are shown in Table 1.
[0084] Table 1 Functional copper foil current collectors prepared in the examples and comparative examples and related properties of batteries prepared therewith
[0085] It can be seen from Table 1 that the functional copper foil current collector provided by the present invention has low residual stress, and also has more suitable bonding force and better tensile strength. It is a functional copper foil current collector with good comprehensive performance. Therefore, the battery prepared therefrom also has a higher cycle capacity retention rate, that is, it has better cycle performance. Please refer to Examples 1 to 10 for details.
[0086] In Comparative Examples 1 and 3, during the process of forming the first copper layer by magnetron sputtering, the deposition rate is too high, resulting in the first copper layer having too large a grain size, and further making the second copper layer having too large a grain size, causing the functional copper foil current collector to have too high a residual stress, and at the same time, the adhesion and tensile properties are also reduced, which ultimately leads to a decrease in the cycle capacity retention rate of the battery prepared therefrom.
[0087] In Comparative Example 2, during the wet electroplating process to form the second copper layer, the deposition rate was too high, resulting in the second copper layer having a too large grain size, and also having some impact on the grain size of the first copper layer, causing the functional copper foil current collector to have excessively high residual stress, while the adhesion and tensile properties also decreased, ultimately leading to a decrease in the cycle capacity retention rate of the battery prepared therefrom.
[0088] In Comparative Example 4, during the process of forming the first copper layer by magnetron sputtering, the deposition rate is too low, resulting in too small grain size of the first copper layer, which will also cause an increase in the residual stress of the functional copper foil current collector, and will also cause a decrease in adhesion and tensile properties, ultimately leading to a decrease in the cycle capacity retention rate of the battery prepared therefrom.
[0089] Further, examples 1 to 5 are observed, where the difference between examples 1 to 3 is that the deposition rate in the process of forming the first copper layer by magnetron sputtering of S1 is different, and the difference between examples 1 and 4 to 5 is that the deposition rate in the process of forming the second copper layer by wet electroplating of S2 is different. When the deposition rate in the process of forming the first copper layer by magnetron sputtering or the deposition rate in the process of forming the second copper layer by wet electroplating is changed, the main changes are the grain size of the first copper layer and the grain size of the second copper layer, and the corresponding grain size of the second copper layer and the grain size of the first copper layer will also be affected to some extent, which will also change the residual stress, tensile strength and bonding force of the functional copper foil current collector, and finally make the cycle performance of the battery slightly different. Among them, the residual stress in the functional copper foil current collector in example 4 is the lowest, and the cycle performance of the battery is the best.
[0090] Furthermore, by observing Examples 6 to 9, it can be found that when the material of the polymer film is changed, the performance of the functional copper foil current collector is also better in various aspects.
[0091] Further, by comparing Example 1 with Example 10, in the example, the deposition rate in the process of forming the first copper layer by regulating magnetron sputtering is relatively high, and the bonding force of the functional copper foil current collector is controlled to be relatively large, so its residual stress is relatively higher than that of Example 1, and the battery cycle performance is also slightly worse.
[0092] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A functional copper foil current collector, characterized in that: It comprises a polymer film, a first copper layer and a second copper layer, wherein the first copper layer is arranged on both sides of the polymer film, and the second copper layer is arranged on the surface of the first copper layer; The residual stress of the functional copper foil current collector is not higher than 5.5 MPa; The thickness d1 of the first copper layer is 50-140 nm, and the grain size a1 is 20-60 nm; The thickness d2 of the second copper layer is 800-1200 nm, and the grain size a2 is 100-200 nm.
2. The functional copper foil current collector according to claim 1, characterized in that: The bonding force of the functional copper foil current collector is 200-300 N / m.
3. The functional copper foil current collector according to claim 1, characterized in that: The thickness of the polymer film is 4-6 μm.
4. The functional copper foil current collector according to claim 1, characterized in that: The material of the polymer film includes at least one of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyethylene, polypropylene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, polyphenylene sulfide, polyphenylene oxide, polystyrene, and polyimide.
5. The method for preparing a functional copper foil current collector according to any one of claims 1 to 4, characterized in that: The steps include: S1. After the polymer film is pre-treated by plasma cleaning, the first copper layer is plated on both sides of the polymer film by magnetron sputtering; during the magnetron sputtering process, the temperature of the polymer film is controlled to be maintained at -18~-22°C, and the magnetron sputtering rate is 1~2nm / s; S2. Then, the second copper layer is plated on both sides of the product obtained in S1 by wet electroplating. During the wet electroplating process, the temperature of the electroplating solution is maintained at 24-26°C, the electroplating rate is 1-3nm / s, and the electroplating rate is controlled to be greater than the magnetron sputtering rate to obtain the functional copper foil current collector.
6. The method for preparing a functional copper foil current collector according to claim 5, characterized in that: In S1, the specific operation of the plasma cleaning pretreatment is: placing the polymer film in a vacuum of 2×10 -4 ~8×10 -3 Under the condition of Pa, argon gas is introduced with a flow rate of 80~100sccm and the processing time is 5~10s.
7. The method for preparing a functional copper foil current collector according to claim 5, characterized in that: In S2, the electroplating solution includes 90~110g / L copper sulfate, 110~130g / L sulfuric acid, 40~60mg / L hydrochloric acid, and 105~350mg / L copper plating additives; the copper plating additives include 50~100mg / L accelerator, 5~50mg / L leveler, and 50~200mg / L inhibitor.
8. The method for preparing the functional copper foil current collector according to claim 7, characterized in that: In S2, the electroplating solution includes 100 g / L copper sulfate, 120 g / L sulfuric acid, 50 mg / L hydrochloric acid, 80 mg / L accelerator, 30 mg / L leveler, and 100 mg / L inhibitor.
9. A pole piece, comprising the functional copper foil current collector according to any one of claims 1 to 4 or the functional copper foil current collector prepared by the method for preparing the functional copper foil current collector according to any one of claims 5 to 8.
10. A battery, comprising the functional copper foil current collector according to any one of claims 1 to 4, or the functional copper foil current collector prepared by the method for preparing the functional copper foil current collector according to any one of claims 5 to 8, or the pole piece according to claim 9.
Citation Information
Patent Citations
Coated part and preparation method thereof, shell and electronic product
CN115261948A
Preparation method of light double-sided roughened special copper foil
CN117845286A
Composite copper foil
CN119252932A
Composite current collector, and manufacturing method therefor and application thereof
WO2024245177A1
Cited By
Gradient CTE high-strength composite current collector and preparation method thereof
CN120319819A
Functional foil current collector and preparation method thereof, pole piece and battery
CN120565687A
Composite current collector and preparation method thereof, lithium metal battery and electric equipment
CN120933382A